Rare case of urethral duplication in the boy - I. M. Kagantsov; I. A. Sannikov; A. V. Golovin; V. G. Svarich (Вестник урологии)
A non-typical variant of Y-type urethral duplication has been described in the article. In this case, the surgical treatment decision was not difficult. Y-type urethral duplication was exposed up to the sinus, and its dissection was performed, followed by urethroplasty. This variant of Y-type urethral duplication has not been described in the world literature available to us, and, in our opinion, it is important for gaining experience in treating rare variants of congenital anomalies of the urethra.